Shaping the Boundaries of a Service Ecosystem: The Case of Udacity - Rothe, Hannes; Steier, Florian (Proceedings of the 50th Hawaii International Conference on System Sciences, 2017)
Service-dominant logic highlights the ability of service ecosystems to ’self-adjust’ as a reaction to sys-temic inefficiencies or external changes [1]–[3]. We contribute to the question on how focal actors shape the boundaries of service ecosystems through service innovation. This is a single case study on a digital eco-system focused on a first mover in digital platforms for Massive Open Online Courses (MOOCs): Udacity. We found two mechanisms, where Udacity shaped the boundaries of its ecosystem: ’user self-service integra-tion’ and ’gradual partner disintegration’. Through-out three phases between 2011 and 2015 they disinte-grated services from higher education, namely offer-ing courses online, designing course, and accredita-tion due to lowly perceived adaptability of universities and external pressures for finding a sustainable busi-ness model. Additionally, they disintegrated self-orga-nized solutions of user needs and re-integrated them with new actors. This led to newly shaped boundaries of the service ecosystem.
Keywords: massive open online course; MOOC; platform; service ecosystem; service ecosystem design; service-dominant logic